To Parents of Children with Special Needs A Manual on Parent Involvement in Educational Programming - Pasanella, Anne Langstaff; Volkmor, Cara B.; California Regional Resource Center, Los Angeles ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
Intended for parents of handicapped children in California, the book contains information on individualized education programing (IEP), parents' rights and responsibilities, and being an advocate. The introduction contains a brief history of special education, a description of the Education for All Handicapped Children Act and the California State Plan for Special Education, and a glossary of special terms. The chapter on the IEP describes the educational programing process (referral, assessment, developing the IEP, placement, instruction, and review) and includes a glossary. The third chapter focuses on parents' rights and responsibilities with emphasis on due process, what it means, and how it works. The final chapter is on being an advocate and includes sections on being involved in the implementation of your child's IEP, exercising your rights, joining a parent organization, becoming a member of a community advisory committee, being an active citizen, and organizing or volunteering to participate in action projects. A list of resources for advocates follows. (DB)
Sponsoring Agency: Bureau of Education for the Handicapped (DHEW/OE), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Advocacy; Disabilities; Due Process; Elementary Secondary Education; Federal Legislation; Glossaries; Individualized Education Programs; Parent Participation; Parent Responsibility; State Legislation; California; Guides, Non-Classroom.; Reference Materials, Vocabularies/Classifications.